2020
DOI: 10.15252/embj.2019103476
|View full text |Cite
|
Sign up to set email alerts
|

Multilineage murine stem cells generate complex organoids to model distal lung development and disease

Abstract: Organoids derived from mouse and human stem cells have recently emerged as a powerful tool to study organ development and disease. We here established a three‐dimensional (3D) murine bronchioalveolar lung organoid (BALO) model that allows clonal expansion and self‐organization of FACS‐sorted bronchioalveolar stem cells (BASCs) upon co‐culture with lung‐resident mesenchymal cells. BALOs yield a highly branched 3D structure within 21 days of culture, mimicking the cellular composition of the bronchioalveolar com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 50 publications
0
51
0
Order By: Relevance
“…Accordingly, this model could be used to study epithelial-mesenchymal crosstalk mechanisms and the role of these subsets within the niche during lung branching. In addition, following treatment of BALO with morpholino oligos against miR-142-3p , a miRNA known to activate the canonical WNT β-catenin pathway, BALO mimicked developmental defects observed in ex vivo embryonic lung implants (Carraro et al, 2014 ; Vazquez-Armendariz et al, 2020 ). Such defects included reduced growth and impaired branching morphogenesis caused by adenomatosis polyposis coli ( Apc ) and β-catenin destruction complex activation.…”
Section: Branching Lung Organoid Modelsmentioning
confidence: 93%
See 2 more Smart Citations
“…Accordingly, this model could be used to study epithelial-mesenchymal crosstalk mechanisms and the role of these subsets within the niche during lung branching. In addition, following treatment of BALO with morpholino oligos against miR-142-3p , a miRNA known to activate the canonical WNT β-catenin pathway, BALO mimicked developmental defects observed in ex vivo embryonic lung implants (Carraro et al, 2014 ; Vazquez-Armendariz et al, 2020 ). Such defects included reduced growth and impaired branching morphogenesis caused by adenomatosis polyposis coli ( Apc ) and β-catenin destruction complex activation.…”
Section: Branching Lung Organoid Modelsmentioning
confidence: 93%
“…BASC contribution to lung regeneration upon different types of injury was recently confirmed by lineage tracing of SFTPC + SCGB1A1 + BASCs in double reporter transgenic mice in vivo (Liu et al, 2019 ; Salwig et al, 2019 ). In an additional study, 3D culture of BASCs (EpCAM high SCA-1 + SCGB1A1 + SFTPC + ) and lung resident mesenchymal cells (rMC) (CD45 − CD31 − EpCAM − SCA-1 + ) isolated from adult mouse lungs gave rise to mainly bronchioalveolar lung organoids (BALO) that exhibit distinct bronchiolar-like structures containing basal, club, goblet, and ciliated cells and alveolar-like structures comprising differentiated AECI and AECII that resembled the proximodistal pattering of the lung ( Figure 1D ) (Vazquez-Armendariz et al, 2020 ). The BALO system contains distinct subsets of rMCs, including myofibroblasts (PDGFRα high αSMA + ) and lipofibroblasts (PDGFRα low LipidTOX + ) that were shown to be indispensable for proximodistal specification, differentiation, and branching formation.…”
Section: Branching Lung Organoid Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even earlier studies using isolated endoderm have shown that recombinant growth factors such as FGF1 or FGF10 are sufficient to induce epithelial branching (Nogawa and Ito, 1995 ; Bellusci et al, 1997 ). Co-culturing bronchioalveolar stem cells (BASCs) characterized by dual expression of airway and alveolar markers ( Scgb1a1 and Sftpc , respectively) with appropriate resident mesenchymal cells (CD45- CD31- EpCAM- SCA-1+) leads to the formation of highly branched bronchioalveolar organoids that are reminiscent of the branching lung (Vazquez-Armendariz et al, 2020 ). Last but not least, several theoretical works have shown that FGFs per se drive lung branching (Miura and Shiota, 2002 ; Clément et al, 2012 ).…”
Section: The Lung Epithelium Is Capable Of Branching In the Absence Omentioning
confidence: 99%
“…To date, these lung organoids are limited in their complexity that they do not recapitulate the complex lung microenvironment and do not include immune and endothelial compartments. In the current issue, Vazquez‐Armendariz et al (2020) report development of a complex mouse bronchioalveolar lung organoid (BALO) system by co‐culturing bronchioalveolar stem cells (BASCs) with defined subsets of lung‐resident mesenchymal cells (rMCs). Subsequently, this study also incorporated tissue‐resident macrophages and explored their effect on epithelial differentiation and maturation in BALO cultures (Fig 1).…”
Section: Figure Schematic Representation Of Balo Culture Modelmentioning
confidence: 99%